Menciptakan Mutu Perguruan Tinggi (Higher Educations) Berskala Internasional Melalui Strategi Penerapan Tata Kelola Universitas Yang Baik (Good University Governance) - Pujiono Pujiono; Made Dudy Satyawan (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2011)
AbstractThis study sought to strip the university in the era of globalization, and the application of good governance. Globalization has changed the university (colleges) that exist in the world vying to become world class University. Most universities (colleges) in Indonesia have transformed itself from the university for teaching to be research university. Several models of approaches can be adopted to implement good governance in the face of global challenges that can be done through a model or framework of bureaucratic, political, collegial, and symbolic. Besides the university (college) should be able to guarantee transparency, accountability, rensponsive, reponsibility, independency, and fairness as well as other additional principle should be in accordance with the vision and mission of the university.